2004
DOI: 10.1016/j.ejcts.2003.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial integrity of ultrasonically skeletonized internal thoracic artery: morphological analysis with scanning electron microscopy

Abstract: The skeletonization of the ITA with an ultrasonic scalpel had no deleterious effect on the endothelium. This morphological study confirmed the safety and the reliability of this technique, and we therefore recommend its clinical use in the skeletonization of the ITA for CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
1
15
1
Order By: Relevance
“…But skeletonization of the ITA preparation is more technically demanding and may be traumatic for the arterial wall. There are few reports explaining the effects of skeletonization on vessel-wall integrity [Deja 1999;Gaudino 1999;Ueda 2003;Yoshikai 2004].…”
Section: Discussionmentioning
confidence: 99%
“…But skeletonization of the ITA preparation is more technically demanding and may be traumatic for the arterial wall. There are few reports explaining the effects of skeletonization on vessel-wall integrity [Deja 1999;Gaudino 1999;Ueda 2003;Yoshikai 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Technically, skeletonization is often criticized for its longer harvesting time [22] and potential risk of damaging the ITA with elektrokoteterizasition [23,24]. Some publications have reported longer harvesting times for skeletonized versus conventional, non-skeletonized conduits, but it can be completed in 25-30 minutes in most cases [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, microscopic analyzes were not performed although they are necessary to better evaluate the method. Lehtola et al [7] and Yoshikai et al [24] demonstrated, by electronic microscopy, that endothelial injuries of the ITA did not occur when USS was used.…”
Section: -Final Aspect Of Skeletonized Internal Thoracic Arterymentioning
confidence: 99%